COMBINING GOOGLE SKETCHUP AND ISPRING SUITE 8: A BREAKTHROUGH TO DEVELOP GEOMETRY LEARNING MEDIA - Nurwijayanti, Ani; Budiyono, Budiyono; Fitriana, Laila (Department of Doctoral Program on Mathematics Education, Sriwijaya University, 2019)
This study aims to develop geometry learning media on curved-solid objects using Ispring Suite 8 with 3D effects supported by Google SketchUp. It also aims to find the effectiveness of the media towards the basic geometry skills and the learning result of 9th-grade students of junior high school. This study is a development study which refers to Budiyono’s development model that includes four stages. These stages are the preliminary, product development, product trial on its effectiveness, dissemination and product implementation. The entire stage was imposed on three different schools in Karanganyar, one of a district in Indonesia, by using stratified cluster random sampling. Within the three schools, we took seven classes to join the effectiveness test through the assessment questionnaire and the before-after test, as well as the efficacy test after the expert's judgement using the validation sheet. The result shows that the geometry learning media is valid based on the experts' validation judgement, and also practical based on the teacher and students’ judgement in the trial of the product. The students’ basic geometry skills and learning result are improved after getting the treatment with the media. Finally, we can conclude that this media is effective and able to be used further in the junior high school level.